Antitrypanosomal screening and cytotoxic effects of selected medicinal plants - Othman, Dyary Hiewa; Abdul Kadir, Arifah; Sharma, Reuben Sunil Kumar; Abdullah, Rasedee; Md. Sukari, Mohd. Aspollah; Zakaria, Zainul Amiruddin; Ahmad, Zuraini; Somchit, Muhammad Nazrul Hakim (Malaysian Society of Parasitology and Tropical Medicine, 2014)
Trypanosoma evansi, the causative agent of “surra”, infects many species of wild and domestic animals worldwide. In the current study, the aqueous and ethanolic extracts of six medicinal plants, namely, Aquilaria malaccensis, Derris elliptica, Garcinia hombroniana, Goniothalamus umbrosus, Nigella sativa, and Strobilanthes crispus were screened in vitro for activity against T. evansi. The cytotoxic activity of the extracts was evaluated on green monkey kidney (Vero) cells using MTT-cell proliferation assay. The median inhibitory concentrations (IC50) of the extracts ranged between 2.30 and 800.97 µg/ml and the median cytotoxic concentrations (CC50) ranged between 29.10 µg/ml and 14.53 mg/ml. The aqueous extract of G. hombroniana exhibited the highest selectivity index (SI) value of 616.36, followed by A. malaccensis aqueous extract (47.38). Phytochemical screening of the G. hombroniana aqueous extract revealed the presence of flavonoids, phenols, tannins, and saponins. It is demonstrated here that the aqueous extract of G. hombroniana has potential antitrypanosomal activity with a high SI, and may be considered as a potential source for the development of new antitrypanosomal compounds.